2019
DOI: 10.1101/758896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical activation of TWIK-related potassium channel by nanoscopic movement and rapid second messenger signaling

Abstract: The transduction of force into a biological signal is critical to all living organisms. Recently, disruption of ordered lipids has emerged as an 'atypical' force sensor in biological membranes; however, disruption has yet to link with canonical channel mechanosensation. Here we show that forceinduced disruption and lipid mixing activates TWIKrelated K + channel (TREK-1), and that this activation is dependent on phospholipase D2 (PLD2). PLD2 transduces the force into a chemical signal phosphatidic acid (PA) tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…Investigating the effect of astrocyte cholesterol on channels will be important for studying AD since many of the palmitoylated channels have profound effects on neuronal excitability and learning and memory 68 . In a separate study we saw apoE and high cholesterol caused the potassium channel TREK-1 to traffic to lipid rafts similar to APP (Nayebosadri unpublished data) 69 and anesthetics 38 and mechanical force disrupts the localization 70 .…”
Section: Discussionmentioning
confidence: 93%
“…Investigating the effect of astrocyte cholesterol on channels will be important for studying AD since many of the palmitoylated channels have profound effects on neuronal excitability and learning and memory 68 . In a separate study we saw apoE and high cholesterol caused the potassium channel TREK-1 to traffic to lipid rafts similar to APP (Nayebosadri unpublished data) 69 and anesthetics 38 and mechanical force disrupts the localization 70 .…”
Section: Discussionmentioning
confidence: 93%
“…The concept that molecules diffuse laterally in the plane of the membrane was first proposed by Roger Kornberg and Harden McConnell in 1971 45 . Decades of research showed that both proteins and lipids contribute to restricted diffusion of lipid in the membrane 46,47 and that the cells use the restricted movement for biological function 25,26,28,48 . The finding here that a virus would be highly dependent on such a process is not unexpected and our proposed membrane protein translocation mechanism could be significant for other viruses.…”
Section: Discussionmentioning
confidence: 99%
“…PLD is known to be sensitive to its localization to lipid domains 5 and recent research has shown that anesthetics have a significant effect on the organization of these domains 2,19,20 . PLD and its activating lipid PA have also been shown to directly control the activity of the mammalian potassium channel TREK-1, a hyperpolarizing channel 7,21 . While it is unknown what channels with which the fly ortholog of PLD are associated, recent experiments have shown that it too is likely helping to regulate a hyperpolarizing channel like TREK-1.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme phospholipase D (PLD) is known to be regulated by localization to lipid domains 5 , and disruption of these domains by anesthetics have shown activation of the enzyme 2 . Since PLD is also known to bind to and regulate the activity of associated ion channels through the production of the signaling lipid phosphatidic acid (PA) 6,7 , we wanted to know if the activation of PLD by anesthetics could play a role in the temporary loss of consciousness commonly attributed to volatile anesthetics. We chose to answer this question using D. melanogaster since this animal only has one copy of the PLD gene and exhibits similar effects to anesthetics as their mammalian counterparts 8 .…”
Section: Introductionmentioning
confidence: 99%